Big Data and Security: A Review of Social Media Risks and Insights for Indonesia - Harakan, Ahmad; Abdillah, Abdillah; Said, Try Gustaf; Mujizatullah, Mujizatullah; Gray, Simon (Universitas Muhammadiyah Yogyakarta, 2024)
This article investigates the complex relationship between big data and management, focusing on the mitigation of potential threats arising from social media platforms, particularly in the Indonesian context. A comprehensive literature review examines existing social media security concerns and mitigation strategies, revealing a notable gap in research regarding effective government policies and plans to address these issues, especially in countries where such frameworks are lacking. This study contributes to the discourse by synthesizing key findings from the literature and offering actionable recommendations to stakeholders for mitigating social media security risks. Furthermore, it identifies practical lessons and proposes avenues for future research to explore strategies and pragmatic perspectives aimed at addressing the potential risks associated with social media for the Indonesian government. The novelty of this research lies in its focus on bridging the gap between big data, social media risks, and the development of effective government policies in the Indonesian context, contributing to a safer and more secure digital landscape.